Numerical Study on Rod Thrust Vector Control for Physical Applications - Dong Li; Kexin Wu (International Journal of Aerospace Engineering)
Mechanical thrust vector control is a classical and significant branch in the thrust vector control field, offering an extremely reliable control effect. In this article, steady-state and unsteady-state aerodynamic characteristics of the rod thrust vector control technology are numerically investigated in a two-dimensional supersonic nozzle. Complex flow phenomena caused by the penetrating rod in the diverging part of the supersonic nozzle are elucidated with the purpose of a profound understanding of this simple flow control technique for physical applications. Published experimental data are used to validate the dependability of current computational fluid dynamics results. A grid sensitivity study is carried through and analyzed. The result section discusses the impacts of two important factors on steady-state aerodynamic features, involving the rod penetration height and the rod location. Furthermore, unsteady-state flow features are analyzed under various rod penetration heights for the first time. Significant vectoring performance variations and flow topology descriptions are illuminated in full detail. While the rod penetration height increases, the vectoring angle increases, whereas the thrust coefficient decreases. As the rod location moves downstream close to the nozzle exit, the vectoring angle and thrust coefficient increase. In terms of unsteady-state aerodynamic effects, certain pressure oscillations occur upstream of the rod, which resulted from the expanding and shrinking of the upstream anticlockwise separation bubbles.